Conflict management styles among nurses at a teaching hospital in Chitwan - Maharjan, Sabita; Shakya, Jayalaxmi (Journal of Chitwan Medical College, 2021)
Background: Nursing professionals are vulnerable to conflict due to nature of work, working environment and diversity of interaction. If conflict management is done properly adopting the effective conflict management style, it would enhance the job morale and promote the effective growth of any health institution. Hence, this study was aimed to find out the conflict management styles among nurses at a Teaching Hospital, Chitwan. Methods: A descriptive cross-sectional study design was used to identify the most preferred conflict management style among 50 nurses at a Teaching Hospital of Chitwan using non-probability convenience sampling method. The data was collected from 6th Dec 2020 till 19th Dec 2020 through self-administered questionnaire and standardized tool of Rahim Organizational Conflict Inventory II. The data analysis was done using descriptive statistics. Results: Among 50 respondents, the median age was 23.0 years. Regarding conflict management, among the five conflict management, collaborating style (4.17±0.38) was the most preferred one followed in rank order by compromising style (3.70±0.52), accommodating style (3.55±0.38), avoiding style (3.27±0.59) and competing style (3.06±0.77). Conclusions: The findings concluded that collaborating and competing style was the most and the least preferred conflict management style respectively while handling conflict among peers during clinical hours. Thus, it is important that nurse managers and hospital authority would pay attention towards promotion of effective conflict management style for nursing professionals through training and in-service education sessions.